2013
DOI: 10.1155/2013/510703
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Endocrine Disrupting Chemicals Serum Levels and White Blood Cells Gene Expression of Nuclear Receptors in a Population of Infertile Women

Abstract: Significant evidence supports that many endocrine disrupting chemicals could affect female reproductive health. Aim of this study was to compare the internal exposure to bisphenol A (BPA), perfluorooctane sulphonate (PFOS), perfluorooctanoic acid (PFOA), monoethylhexyl phthalate (MEHP), and di(2-ethylhexyl) phthalate (DEHP) in serum samples of 111 infertile women and 44 fertile women. Levels of gene expression of nuclear receptors (ERα, ERβ, AR, AhR, PXR, and PPARγ) were also analyzed as biomarkers of effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…In particular , increased BPA levels are correlated with a decrease in peak estradiol levels and decreased oocyte retrieval number [10,44]. A similar mechanism of action may underlie the association between female infertility and higher BPA levels that has been consistently reported in the results of the Italian biomonitoring study PREVIENI [11,45]. Interestingly, in this study, the higher serum BPA levels in infertile women were also correlated with upregulation of some nuclear receptors (ERα, ERβ, Androgen receptor, and Pregnane-X receptor) in the serum mononuclear cells [11,45].…”
Section: Methodsmentioning
confidence: 85%
“…In particular , increased BPA levels are correlated with a decrease in peak estradiol levels and decreased oocyte retrieval number [10,44]. A similar mechanism of action may underlie the association between female infertility and higher BPA levels that has been consistently reported in the results of the Italian biomonitoring study PREVIENI [11,45]. Interestingly, in this study, the higher serum BPA levels in infertile women were also correlated with upregulation of some nuclear receptors (ERα, ERβ, Androgen receptor, and Pregnane-X receptor) in the serum mononuclear cells [11,45].…”
Section: Methodsmentioning
confidence: 85%
“…[40,41] Since both phthalates and PFASs show toxicity and prolonged exposure can affect endocrine function and cause neurodevelopmental disorders and infertility we have calculated the estimated daily ingestion of the contaminants of interest through tuna consumption. [42][43][44][45][46][47][48][49] The tolerable daily intake (TDI) established for DEHP is 0.05 mg/kg, a value that was used in this work as a basis of comparison for the intake of DEHP itself and for the total amount of DEHP and MEHP, being the latter a direct metabolite of DEHP. [12] We calculated the EDI for the general Italian population and for those who claimed to be fish consumers, assuming that their daily fish intake consisted solely of Atlantic bluefin tuna fillets (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…It suggests that BPA is able to disturb uterine environments with respect to aberrant expression of genes important for embryo implantation. In fact, a recent study showed that infertile women tend to have significantly detectable serum BPA compared to women with proven fertility [34]. Interestingly, the women with the relatively higher levels of BPA in their urine had possibility to have twice the chance of implantation failure [13].…”
Section: Discussionmentioning
confidence: 99%